NF-κB Pathway as a Potential Target for Treatment of Critical Stage COVID-19 Patients - Kircheis, Ralf; Haasbach, Emanuel; Lueftenegger, Daniel; Heyken, Willm T.; Ocker, Matthias; Planz, Oliver (Frontiers in Immunology, 2020)
Patients infected with SARS-CoV-2 show a wide spectrum of clinical manifestations ranging from mild febrile illness and cough up to acute respiratory distress syndrome, multiple organ failure and death. Data from patients with severe clinical manifestations compared to patients with mild symptoms indicate that highly dysregulated exuberant inflammatory responses correlate with severity of disease and lethality. Epithelial-immune cell interactions and elevated cytokine and chemokine levels, i.e. cytokine storm, seem to play a central role in severity and lethality in COVID-19. The present perspective places a central cellular pro-inflammatory signal pathway, NF-kappaB, in the context of recently published data for COVID-19 and provides a hypothesis for a therapeutic approach aiming at the simultaneous inhibition of whole cascades of pro-inflammatory cytokines and chemokines. The simultaneous inhibition of multiple cytokines/chemokines is expected to have much higher therapeutic potential as compared to single target approaches to prevent cascade (i.e. triggering, synergistic, and redundant) effects of multiple induced cytokines and chemokines in critical stage COVID-19 patients.